1995
DOI: 10.1037/0021-9010.80.6.721
|View full text |Cite
|
Sign up to set email alerts
|

Role of ability and prior knowledge in complex training performance.

Abstract: A causal model of the role of general cognitive ability and prior job knowledge in subsequent job-knowledge acquisition and work-sample performance during training was developed. Participants were 3,428 U.S. Air Force officers in pilot training. The measures of ability and prior job knowledge came from the Air Force Officer Qualifying Test. The measures of job knowledge acquired during training were derived from classroom grades. Work-sample measures came from check flight ratings. The causal model showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 27 publications
5
104
0
1
Order By: Relevance
“…We averaged scores on the two tests to obtain a measure of general cognitive ability (see Ree et al, 1995).…”
Section: Predictor Measuresmentioning
confidence: 99%
“…We averaged scores on the two tests to obtain a measure of general cognitive ability (see Ree et al, 1995).…”
Section: Predictor Measuresmentioning
confidence: 99%
“…Over the last 20 years, the Air Force has been consistent in selecting pilots with high intellectual ability. Student pilots with high scores on ability tests are more likely to complete training (Olea & Ree, 1994;Ree, Carretta, & Teachout, 1995) and learn to fly with fewer hours in training air craft (Duke & Ree, 1996) yielding substantial benefits to the Air Force. These results are consistent with previous studies assessing the intellectual performance and capabilities of USAF pilots and pilot applicants with respect to the normative population (Retzlaff, Callister, & King, 1999;Retzlaff & Gibertini, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, each year there are several aviation related mishaps in training and operational missions where human error is often considered a causal factor. As a result of the high risk nature of military flying and the evidence that a pilot's cognitive disposition is crucial for safe and effective flying, the cognitive assessment of USAF pilots is a critical part of medical flight screening and the aeromedical waiver process (Olea & Ree, 1994;Ree, Carretta, & Teachout, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Warr and Bunce identified this relationship between prior job knowledge and pretraining motivation as needing further research. Ree, Carretta, and Teachout (1995) also performed research that included studying the relationship of prior job knowledge and training transfer. Results of the study indicated that prior job knowledge had little influence on subsequent job knowledge, but had direct influence on early work outcomes, which in turn influenced training transfer.…”
Section: Prior Job Knowledgementioning
confidence: 99%